Service Quality and its Influence on Service Excellence and Customer Satisfaction with Water Provision in Nyandeni Municipality - Lubuzo, Zintle; Mapuranga, Miston (International Review of Management and Marketing, 2026)
Service quality is a critical determinant of organisational success and customer satisfaction, particularly in essential public utilities like water provision. This study examines the impact of service quality dimensions on service excellence and customer satisfaction within Nyandeni Municipality, Eastern Cape, South Africa, a region facing significant challenges in its water service provision. Through a quantitative cross-sectional design, data were collected from 380 residents using a structured questionnaire and analysed via Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that Assurance, Empathy, and Reliability are significant drivers of Service Excellence, while Tangibility and Responsiveness show insignificant impacts. Service Excellence itself emerges as a powerful predictor of Customer Satisfaction (β = 0.777), accounting for 73.8% of its variance. The model demonstrates strong explanatory power, with Service Excellence explained by 80.8% of the variance from the five service quality dimensions. These results underscore that achieving customer satisfaction in municipal water provision requires a focused strategy on building trust, demonstrating care, and ensuring dependable service. The study provides a validated framework for municipal policymakers and water service managers to enhance service delivery, optimise resource allocation, and foster public trust in rural contexts, contributing valuable insights to the literature on public service quality and sustainable development.